ETHICS PRACTICES AMONG IT PROFESSIONAL AN EMPIRICAL ASSESSMENT. - Mishra, Alok (International Journal of Ethics (1556-4444), 2008)
Information systems ethical issues are important to all its users, organizations, socities and significantly to Information Technology (IT) professionals. Although, there is considerable literature on IT and related ethical issues, there is little empirical research on ethics practices among IT professionals in organizations. This paper reviews and discusses ethical issues in general and then reports the findings of a survey concerning the relationship between demographic factors and ethical use of IT in Turkey. The survey was conducted among IT professionals from government and private sector organizations. Based on this survey, the results indicated that age, experience and use of the Internet have significant impact on ethical use of IT.